Harapan Pemuda Desa Pasir Angin sebagai bagian dari Bisnis Pariwisata di Lingkungan sekitar Desa - Ningrum, Lestari (Jurnal Pemberdayaan Pariwisata, 2020)
The existence of a village in the tourism business environment, ideally, can help the village develop, the villagers can prosper to follow the development of the tourism business, which can be part of business people in the tourism business, both as workers and supporters. Through a community service program, the private sector seeks to foster with one of them providing counseling in the form of skills training aimed at supporting villagers to take a role in the tourism business in their neighborhood. Community Sevices is done by the method of observation, focus group discussions and conducting training. Villagers have hopes and desires, but in life, not always all can be realized, especially in fostering a village it is necessary to have cooperation in which each party carries out their respective functions (The golden Triangel). So, even though community service activities have been carried out, the ultimate goal cannot always be realized, the role of citizens who have also been carried out by private parties who have carried out their functions does not guarantee the realization of the hopes of villagers, the local government must also play its function.